Vitamin D deficiency and causative factors in the population of Tehran - Hamidi Zohreh; Shafaei Ali; Soltani Akbar; Pajouhi Mohammad; Sedaghat Mojtaba; Javadi Ebrahim; Adibi Hossein; Larijani Bagher; Hashemipour Sima; Fard Ali; Hossein-Nezhad Arash; Booya Fargol (BMC, 2004)
Abstract Background There are multiple studies in different countries regarding the prevalence of vitamin D deficiency. These studies showed high prevalence of vitamin D deficiency in Asian countries. This study tries to elucidate the prevalence of vitamin D deficiency and its influencing factors in population of Tehran. Methods 1210 subjects 20-64 years old were randomly selected. 25 (OH) D serum levels were measured. Duration of exposure to sunlight, the type of clothing and level of calcium intake and BMI were quantified based on a questionnaire. Results A high percentage of vitamin D deficiency was defined in the study population. Prevalence of severe, moderate and mild Vitamin D deficiency was 9.5%, 57.6% and 14.2% respectively. Vitamin D serum levels had no significant statistical relation with the duration of exposure to sunlight, kind of clothing and BMI. Calcium intake in the normal vitamin D group was significantly higher than the other groups (714.67 ± 330.8 mg/day vs 503.39 ± 303.1, 577.93 ± 304.9,595.84 ± 313.6). Vitamin D serum levels in young and middle aged females were significantly lower than the older group. Conclusions Vitamin D deficiency has a high prevalence in Tehran. In order to avoid complications of vitamin D deficiency, supplemental dietary intake seems essential.